Functional outcomes of proximal femoral locking plate versus proximal femoral nail in subtrochanteric femur fractures - Rahman, M. Mostafizur; Rahman, Nabina; Moniruzzaman, M.; Hasan, S. M. Raqibul; Chowdhury, Golam M.; Haque, S. M. Faisal; Hassan, S. M. Mainul; Khan, M. Ruhul A. (International Journal of Research in Orthopaedics, 2025)
Background: Subtrochanteric femur fractures are difficult to manage because of strong deforming muscular forces and high rates of implant failure. Although several fixation devices are available, the optimal choice remains debated. This study compared the functional outcomes of proximal femoral locking plate (PFLP) and proximal femoral nail (PFN) in subtrochanteric femur fractures. Methods: A prospective observational study was carried out at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, from September 2019 to March 2022. Forty-four patients were included, where 22 treated using PFLP and 22 with PFN. Demographic and clinical data were recorded. Outcomes were assessed by radiological union, limb length discrepancy (LLD), hip pain, range of motion (ROM), Harris hip score (HHS), and complication rates. Results: Union occurred significantly earlier with PFN (13.5±3.2 weeks) than with PFLP (15.6±3.1 weeks; p=0.007). Mean LLD was lower in PFN (0.2±0.33 cm) than in PFLP (0.43±0.47 cm; p=0.0003). Pain-free status was more common in PFN patients (63.6%) compared with PFLP (31.8%). Hip ROM was similar in both groups. However, mean HHS was significantly higher in PFN at final follow-up (89.2±10.1 versus 83.6±12.9; p=0.04). Excellent outcomes were more frequent with PFN (51.9%) than with PFLP (36.4%). Complications were fewer in the PFN group. Conclusion: PFN offers superior functional outcomes and fewer complications compared with PFLP, supporting PFN as the preferred implant for subtrochanteric femur fractures.